2013
DOI: 10.3928/01913913-20130226-01
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Ocular Deviation in Esotropic Subjects Under General Anesthesia

Abstract: The ocular position under general anesthesia was reported as a key factor in the surgical treatment of subjects with esotropia; therefore, its clinical determinants were assessed. The authors observed that preoperative ocular deviation and patient age were the main factors that influenced the ocular position under general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For strabismus surgeons, the development of unexpected ocular deviation under general anesthesia can raise two questions: First, do I need to change the surgical plan? A previous study recommended that surgeons should rely on their preoperative measurements, despite the grossly different amount of deviation under general anesthesia than expected [3]. In the present case, the surgery was performed as planned preoperatively because both eyes showed the same upward deviation and the patient did not show any restrictive pattern at the preoperative measurement.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For strabismus surgeons, the development of unexpected ocular deviation under general anesthesia can raise two questions: First, do I need to change the surgical plan? A previous study recommended that surgeons should rely on their preoperative measurements, despite the grossly different amount of deviation under general anesthesia than expected [3]. In the present case, the surgery was performed as planned preoperatively because both eyes showed the same upward deviation and the patient did not show any restrictive pattern at the preoperative measurement.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies reported changes in ocular position during general anesthesia, and some attempted to evaluate the use of these changes in ocular position to improve surgical outcomes [1][2][3][4]. Moreover, others reported different changes in the ocular position (fixed, eccentrically upward deviation) under general anesthesia [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that esotropias release was all the more important when a child is young at the time of surgery. 3 Thus, tonus decrease might be responsible for spontaneous esotropias release with time and exoshift tendency after surgeries that don't take this parameter in account.…”
Section: Discussionmentioning
confidence: 99%
“…The tonic component refers to a dynamic, innervational force that encompasses Maddox vergences. This tonic component has the specificity to only be present in the awake phase, being suppressed by GA. 2,3,6 This is one explanation of the decrease in the angle of esotropias under GA. Moreover, two identical esotropias in the awake phase can deeply differ under GA, depending on which component is prevalent.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation